The Influence of Election Supervisory Behavior on the Performance of the Regional Head Election Organizer in North Sumatera Province - Sitorus, Monang (Jurnal Ilmiah Peuradeun, 2018)
The purpose of this research is to analyze the influence of behavior of regency/municipality election supervisor on the performance of the election organizer of a regional head (election) in North Sumatera Province. The basis of behavioral theory used in accordance with the phenomena observed in the field is the theory of behavior in which there are dimensions of encouragement, motivation, attitudes, and values ​​with the originator of Mar'at. While the theory of performance using Ruky S Achmad's theory which includes dimensions of quality, quantity, timeliness, cooperation, and responsibility. The method used is survey method with a census. Then, the data is tabulated and analyzed using multiple regressions. The results showed that the biggest dimension of behavior contributing to the performance of the election organizer is the dimension of encouragement (X1) of 1,612, the value (X2) of 1.541, the motivation (X3) of 0.978 and the attitude (X4) of 0.803. While the determination coefficients test (R2) amounted to 83.4%. Other undetectable factors (ε / epsilon) contributed to the election performance of 16.6%.